2013
DOI: 10.1177/0025802413487903
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between NHS performance indicators and suicide rates

Abstract: The negative findings suggest that the performance rating of mental health trusts do not influence local suicide rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For example, depression increases violent behavior and suicidal ideation, 30 while high levels of emotional, cognitive, and mental health buffer bullying, suicidal ideation, and behavior. 31 A survey of Chinese adolescents showed that those with poorer mental health had higher suicidal attitudes, which in turn promoted greater suicidal ideation; 32,33 those with major depressive and anxiety disorders had a higher smoking intensity; and those with poorer mental health had higher rates of truancy and being prone to alcohol abuse. 34 A survey on the participation of ethnic minority students in risky behaviors in Malaysia showed that mental health conditions played an important role in predicting deviant behaviors such as smoking, alcohol consumption, and illegal drug use among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, depression increases violent behavior and suicidal ideation, 30 while high levels of emotional, cognitive, and mental health buffer bullying, suicidal ideation, and behavior. 31 A survey of Chinese adolescents showed that those with poorer mental health had higher suicidal attitudes, which in turn promoted greater suicidal ideation; 32,33 those with major depressive and anxiety disorders had a higher smoking intensity; and those with poorer mental health had higher rates of truancy and being prone to alcohol abuse. 34 A survey on the participation of ethnic minority students in risky behaviors in Malaysia showed that mental health conditions played an important role in predicting deviant behaviors such as smoking, alcohol consumption, and illegal drug use among adolescents.…”
Section: Introductionmentioning
confidence: 99%